The Teaching and Learning Cultural Competence in a Multicultural Environment (CCMEn) Model - Isabel Antón-Solanas; Margarida Coelho; Isabel Huércanos-Esparza; Valérie Vanceulebroeck; Indrani Kalkan; Raul Cordeiro; Nuran Kömürkü; Teresa Soares-Coelho; Nadia Hamam-Alcober; Shana Dehaes; Antonio Casa-Nova; Lucía Sagarra-Romero (MDPI AG, 2020)
Background: Within the European higher education context, students and lecturers are encouraged to engage in teaching and learning activities abroad. This frequently involves using a second language and being exposed to students and lecturers from culturally different backgrounds. Objective: To design a model for teaching and learning cultural competence in a multicultural environment (CCMEn). Design: Theory development from empirical experience, research, and scholarly works. Method: This model was developed based on our experience of teaching and learning cultural competence in a multicultural environment in a nursing education context; it rests on three pillars, namely, Coyle's Content and Language Integrated Learning educational approach, the concept of social and emotional learning, as defined by the Collaborative for Academic, Social and Emotional Learning, and the existing literature surrounding teaching and learning cultural competence in higher education. Results: The CCMEn model is intended to guide the process of teaching and learning cultural competence in a multicultural environment through the use of a second language and has been adapted from existing educational approaches and theory. Conclusion: Teaching and learning in multilingual and multicultural contexts in Europe is becoming more common. Students who learn alongside students and teachers from different cultural backgrounds need to be supported from an academic, linguistic and socioemotional perspective. We believe that the CCMEn model can serve as a guide to enhancing student learning in this context.